E-MARKETING: DISTRIBUTION OF BOOKS BY UNIVERSITY PUBLISHERS - Ali, Ruziah; Abd Razak, Ahmad Zainal Abidin; Mohamad Yusof, Abdul Raheem; Bani Hashim, Ahmad Yusairi (Journal of Human Capital Development (JHCD), 2013)
E-Marketing is a process of delivering information, communicating, promoting, and selling products and services through the internet. The introduction of this technique has caused a drastic change in the method for traditional marketing, by which a company that adopts this technique would find itself sustainable. In Malaysia, there are four focused public universities for engineering and technology programs, known as the Malaysian Technical University Network (MTUN). The publishers of these universities are entrusted with the tasks to produce technical reading and reference materials written by the academic staff. However, though the number of publications is increasing, the sales are not encouraging. It was hypothesized that the number of personnel in the department affects the department’s outputs. Therefore, this paper studies the problems in the publishing departments of these universities and the potential of e-Marketing as a tool to increase sales.